Jollas oklanderae n. sp., a new beetle-like spider from Northeast Argentina (Araneae: Salticidae: Sitticini) - Baigorria, Julián Emanuel Martín (2024)
Within the diverse South American fauna of jumping spiders, the genus Jollas comprises small spiders, generally associated with grasslands or flooded areas and rocky areas with bare soil. In Argentina, six species are known for this genus. In the present work, we describe a new species of Jollas for the north of the country, with unique beetle mimicry features.